2009
DOI: 10.1186/1471-2164-10-19
|View full text |Cite
|
Sign up to set email alerts
|

Genic regions of a large salamander genome contain long introns and novel genes

Abstract: Background: The basis of genome size variation remains an outstanding question because DNA sequence data are lacking for organisms with large genomes. Sixteen BAC clones from the Mexican axolotl (Ambystoma mexicanum: c-value = 32 × 10 9 bp) were isolated and sequenced to characterize the structure of genic regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
90
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 65 publications
(53 reference statements)
7
90
0
Order By: Relevance
“…3a, Supplementary Information section 4.3), a trend that was previously observed in five genes obtained from selective bacterial artificial chromosome sequencing of the axolotl genome 13 . Figure 3b shows a typical gene organization in axolotl compared to its human orthologue.…”
Section: Expansion Of Long Terminal Repeat Retroelementsmentioning
confidence: 59%
“…3a, Supplementary Information section 4.3), a trend that was previously observed in five genes obtained from selective bacterial artificial chromosome sequencing of the axolotl genome 13 . Figure 3b shows a typical gene organization in axolotl compared to its human orthologue.…”
Section: Expansion Of Long Terminal Repeat Retroelementsmentioning
confidence: 59%
“…It is also the rationale behind the new global bioinformatic and systems biology approaches that integrate the molecular elements of large genomic and proteomic databases into functional networks and pathways from which hypotheses about mechanisms emerge (Nabel, 2009). For example, global genomic and proteomic data on blastema formation in regenerating anuran and urodele limbs has been generated by a number of laboratories Habermann et al, 2004;Putta et al, 2004;Grow et al, 2006;Pearl et al, 2008;Smith et al, 2009;Monaghan et al, 2009;Rao et al, 2009) and in one case transcription factor pathways have been subjected to a systems biology analysis (Jhamb et al, 2011).…”
Section: New Approaches and Challengesmentioning
confidence: 99%
“…As the majority of publicly available axolotl genomic data comes from expressed sequence tag (EST) sequencing, and as the average intron length in the axolotl genome is greater than 10 kb (Smith et al, 2009), only a subset of targets found within EST sequences are spaced sufficiently far from intron-exon boundaries to be reliably detected with PCR-based methods. Rapid, endonuclease-based methods of screening pooled PCR products cannot be used to assess mutation frequency when putative mutation sites are near the edges of small PCR products.…”
Section: Rgn Target Selection and Detection Of Indels In The Axolotlmentioning
confidence: 99%
“…The axolotl is not widely adopted as a genetic model organism due to its slow development, its late age of sexual maturity (>1 year), and its exceptionally large (∼3.2×10 10 bp) and currently unsequenced genome (Smith et al, 2009). To overcome these drawbacks, the ideal practical system for investigating gene function in this organism must meet several seemingly daunting requirements.…”
Section: Introductionmentioning
confidence: 99%